2016
DOI: 10.1007/s00429-016-1245-6
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal and ventral stream contributions to form-from-motion perception in a patient with form-from motion deficit: a case report

Abstract: The main model of visual processing in primates proposes an anatomo-functional distinction between the dorsal stream, specialized in spatio-temporal information, and the ventral stream, processing essentially form information. However, these two pathways also communicate to share much visual information. These dorso-ventral interactions have been studied using form-from-motion (FfM) stimuli, revealing that FfM perception first activates dorsal regions (e.g., MT+/V5), followed by successive activations of ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…Our statistical results showed that the higher-level visual cortical area 21a at the ventral stream of pathway and area PMLS at the dorsal stream had a comparable proportion of feedback neurons that back-projected directly to the V1 area, and the distribution of feedback neurons in these two higher-level visual areas was similar at cortical layer II-III, IV, V, and VI. These results suggest that the ventral and dorsal visual streams may closely interact through the V1 area during information processing, which is consistent with previous studies (Shen et al, 2006;Gilaie-Dotan et al, 2013;Zachariou et al, 2014;Huang et al, 2017;Mercier et al, 2017) and argues against the proposition of ventral vs. dorsal pathway segregation (Brown, 2009;Bracci and Op de Beeck, 2016;Milner, 2017). Further, this study also quantitatively compared the proportion of feedback neurons among different high-level visual cortical areas.…”
Section: Characteristics Of Feedback Neurons In the High-level Visualsupporting
confidence: 91%
See 1 more Smart Citation
“…Our statistical results showed that the higher-level visual cortical area 21a at the ventral stream of pathway and area PMLS at the dorsal stream had a comparable proportion of feedback neurons that back-projected directly to the V1 area, and the distribution of feedback neurons in these two higher-level visual areas was similar at cortical layer II-III, IV, V, and VI. These results suggest that the ventral and dorsal visual streams may closely interact through the V1 area during information processing, which is consistent with previous studies (Shen et al, 2006;Gilaie-Dotan et al, 2013;Zachariou et al, 2014;Huang et al, 2017;Mercier et al, 2017) and argues against the proposition of ventral vs. dorsal pathway segregation (Brown, 2009;Bracci and Op de Beeck, 2016;Milner, 2017). Further, this study also quantitatively compared the proportion of feedback neurons among different high-level visual cortical areas.…”
Section: Characteristics Of Feedback Neurons In the High-level Visualsupporting
confidence: 91%
“…It is traditionally assumed that visual information is processed in a feedforward hierarchical model that simple visual features are coded at the primary (V1) or low-level visual cortex, and complex visual attributes converged at higher-order visual areas for perceptual output (Juan and Walsh, 2003;Ro et al, 2003;Briggs and Usrey, 2011;Klink et al, 2017). Specifically, different visual representations are formed along segregated parallel pathways, with object shape or form information processed by the ventral stream from area V1→V3→V4 and motion/spatial location signatures processed by the dorsal stream from V1→V2→V5 (Lehky and Sereno, 2007;Brown, 2009;Kravitz et al, 2011;Mercier et al, 2017). Similar ventral and dorsal visual streams are also defined in the cat after the homolog area 17, 18, 19, 21a and PMLS are equated with V1, V2, V3, V4, and V5 based on electrophysiology evidence and area-specific behavioral observations (Dreher et al, 1993(Dreher et al, , 1996bPayne, 1993;Wang et al, 2000Wang et al, , 2007Shen et al, 2006;Tong et al, 2011;Connolly et al, 2012).…”
Section: Characteristics Of Feedback Neurons In the High-level Visualmentioning
confidence: 99%
“…In visual neuroscience, one well‐received idea is the two visual systems theory, which holds that separate dorsal and ventral pathways play distinct roles in perceiving forms, faces, movements, and actions (Becker‐Bense et al, ; Braddick, OʼBrien, Wattam‐Bell, Atkinson, & Turner, ; Caclin et al, ; Donner, Sagi, Bonneh, & Heeger, ; Farivar, Blanke, & Chaudhuri, ; Handa & Mikami, ; Handa, Unno, & Mikami, ; Hsu et al, ; Keizer, Colzato, & Hommel, ; Lewald & Getzmann, ; Lichtensteiger, Loenneker, Bucher, Martin, & Klaver, ; Mercier, Schwartz, Spinelli, Michel, & Blanke, ). Another widely accepted idea is the notion of the visual word form area (VWFA), which is a brain region that specializes in identifying and processing words (Aquilina et al, ; Boukrina, Hanson, & Hanson, ; Glezer, Kim, Rule, Jiang, & Riesenhuber, ; Proverbio, Zotto, & Zani, ; Vogel, Petersen, & Schlaggar, ; Wang, Caramazza, Peelen, Han, & Bi, ; Xu, Jiang, Ma, Yang, & Weng, ).…”
Section: Potential Educational Benefits Of Applying Findings From Vismentioning
confidence: 99%
“…There is increasing evidence from lesion studies to suggest that the ventral and dorsal cortical areas are essential for SFM perception. Damage to the ventral or dorsal cortical regions in humans is related to SFM perception deficits (Mercier, Schwartz, Spinelli, Michel, & Blanke, ; Schenk & Zihl, ). Deficits in SFM recognition (motion‐defined letter) have been found in humans with lesions in parietotemporal white matter, which corresponds to Brodmann areas 18, 19, 37, 39, 21, and 22.…”
Section: Psychophysical and Lesion Studies: Visual Motion Is The Mostmentioning
confidence: 99%
“…Functional MRI and event‐related potential mapping in human brains have implicated the ventral and dorsal visual pathways in motion‐defined shape perception (for review, see Kourtzi, Krekelberg, & Van Wezel, ). The dorsal visual area MT+/V5, which corresponds with the monkey MT, as well as ventral and lateral occipital areas such as the LOC and ventral occipitotemporal cortex, which are considered to correspond with the monkey ITC, showed SFM‐related activation (Gulyas, Heywood, Popplewell, Roland, & Cowey, ; Mercier et al., ; Schoenfeld et al., ; Wang et al., ). Neuroimaging studies uncovered the involvement of multiple cortical areas in dorsal and ventral pathways, such as V3, the fundus of the superior temporal sulcus, and PPC in addition to V2, V4 and MT, in the processing of three‐dimensional structure‐from‐motion (for review, see Orban, ).…”
Section: Early Cortical Areas Likely Provide a Key Function To Share mentioning
confidence: 99%